Hiring discrimination based on national origin and religious closeness: Results from a field experiment in the Paris area - Guillaume Pierné (IZA Journal of Labor Economics, 2013)
This study uses the findings of a test carried out by correspondence in order to assess separately the potential hiring effects of North African origin and Muslim or Catholic religious affiliation in the French real estate sector. We constructed six jobseeker profiles, each representing a particular situation with respect to national origin and religious closeness, and we sent 1800 resumés in reply to 300 job vacancies advertised from mid April to mid September 2011 in Paris and its suburbs. We find evidences of significant hiring discrimination against applicants of North African origin, regardless of their religious closenesses and against applicants signaling closeness to the Muslim religion, regardless of their national origin.
Keywords: C81; C93; J15; J71; 330; Discrimination; Correspondence testing; Ethnic origin; Religion